Pengembangan Video Pembelajaran Desain Interaksi Berbasis Microlearning untuk Mahasiswa Jurusan Sistem Informasi - Li Cen; Jenny Tan; Tony Tan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The rapid development of digital technology demands more efficient learning strategies, particularly for Information Systems students who often struggle to understand material delivered through conventional methods. This study aims to design and evaluate microlearning-based instructional videos on interaction design with a duration of less than two minutes to enhance student comprehension. The Multimedia Development Life Cycle (MDLC) framework was employed, consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Data were obtained through interviews, expert validation, student assessments, and a Paired Sample T-test administered to 10 Information Systems students using pre-test and post-test instruments. Expert validation produced a feasibility score of 3.6, while students rated the videos at 4.4, indicating that the material was perceived as engaging, clear, and easy to understand. The T-test results showed a Sig. (2-tailed) value of 0.017 (< 0.05), confirming a significant difference between pre-test and post-test scores. These findings demonstrate that ultra-short microlearning videos effectively improve students’ understanding of interaction design concepts. Furthermore, this study contributes to the existing literature by addressing the research gap regarding the effectiveness of ultra-micro content in the context of interaction design learning.